Community Empowerment in the Disadvantaged Village Through an Integrated Student Community Service Program - Marwan, Syaiful; Putera, Wawan (CV Berkah Syahdin Trust, 2025)
Background: Disadvantaged villages often face challenges such as low levels of education and limited access to technology, which hinder community welfare and development. These conditions also affect the quality of early childhood education (PAUD) as part of basic community services, requiring an integrated and asset-based approach to optimize local potential. Aims: This community service aims to empower communities in disadvantaged village areas through an integrated Student Community Service Program (KKN). Methods: This program employed the Asset-Based Community Development (ABCD) approach, which focuses on leveraging local assets and community potential as the foundation for development. The program was implemented through participatory stages, including asset mapping, program planning based on local potential, implementation of activities such as skill training, digital literacy enhancement, and educational support, as well as evaluation and monitoring to ensure sustainability. Result: The program contributed to strengthening community capacity by identifying and utilizing local assets to support educational and economic activities. Students acted as facilitators, collaborating with the community to develop skills, improve digital literacy, and optimize local potential, which in turn supported the improvement of early childhood education practices. Conclusion: The integrated KKN program based on the ABCD approach is effective in empowering communities by utilizing local strengths. This approach not only enhances community welfare but also supports sustainable development in early childhood education.